The impact of ownership concentration on firm sustainability: evidence from Malaysian top 200 public listed firms - Norazlin, Ahmad; Irene, Wei Kiong Ting; Mohd Ridzuan, Darun (Inderscience Enterprises Ltd., 2020)
Larger companies cannot escape from facing financial distress, which eventually leads to insolvency and unsustainability. In this regard, this study examined the relationship between ownership concentration and firm sustainability of top 200 Malaysian public listed companies for the period between the years 2009 and 2015. The two-stage least squares regression results of this study showed that ownership concentration was significantly and negatively related to firm sustainability. This finding remained the same when different proxies of ownership concentration and firm sustainability were used. Generally, this finding indicated that excessive concentrated ownership may lead to decisions that did not satisfy all key shareholders, and may reduce the level of firm sustainability.